2000
DOI: 10.1046/j.1365-4362.2000.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous histoplasmosis associated with acquired immunodeficiency syndrome (AIDS)

Abstract: A 30‐year‐old man, who had originally been admitted to the Centro Dermatológico Pascua for medical attention and was later transferred to the Hospital General de México, presented with a 2‐month history of progressive dermatosis affecting the head (face, ear lobes, oral cavity), trunk (all faces), upper and lower limbs (including the palms and soles), external genitalia, and the perianal region. The patient had no history of homosexuality, but did have a long history of sexual intercourse with prostitutes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Several authors mention that the dermatoses in DCH present with papules and crusting plaques. This clinical picture is common and has been reported previously in Latin American populations 16,17 . Other lesions have been reported such as punch ulcers, purpuric lesions and localized or generalized dermatitis 3,13,18,19 .…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Several authors mention that the dermatoses in DCH present with papules and crusting plaques. This clinical picture is common and has been reported previously in Latin American populations 16,17 . Other lesions have been reported such as punch ulcers, purpuric lesions and localized or generalized dermatitis 3,13,18,19 .…”
Section: Discussionsupporting
confidence: 60%
“…Recent studies have shown liposomal amphotericin B to be more effective 14,25 . In patients who do not need to be admitted to hospital, treatment consists of itraconazole 200 mg three times daily for 3 days, followed by 200 mg twice daily for 12 weeks 16,24 . Another therapeutic option is fluconazole 800 mg/day with follow‐up of patients to monitor and avoid relapses 25 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations